A molecular switch in the scaffold NHERF1 enables misfolded CFTR to evade the peripheral quality control checkpoint - Loureiro, Cláudia (2015)
The peripheral protein quality control (PPQC) checkpoint removes improperly folded proteins from the plasma membrane through a mechanism involving the E3 ubiquitin ligase CHIP (carboxyl terminus of Hsc70 interacting protein). PPQC limits the efficacy of some cystic fibrosis (CF) drugs, such as VX-809, that improve trafficking to the plasma membrane of misfolded mutants of the CF transmembrane conductance regulator (CFTR), including F508del-CFTR, which retains partial functionality. We investigated the PPQC checkpoint in lung epithelial cells with F508del-CFTR that were exposed to VX-809. The conformation of the scaffold protein NHERF1 (Na(+)/H(+) exchange regulatory factor 1) determined whether the PPQC recognized "rescued" F508del-CFTR (the portion that reached the cell surface in VX-809-treated cells). Activation of the cytoskeletal regulator Rac1 promoted an interaction between the actin-binding adaptor protein ezrin and NHERF1, triggering exposure of the second PDZ domain of NHERF1, which interacted with rescued F508del-CFTR. Because binding of F508del-CFTR to the second PDZ of NHERF1 precluded the recruitment of CHIP, the coexposure of airway cells to Rac1 activator nearly tripled the efficacy of VX-809. Interference with the NHERF1-ezrin interaction prevented the increase of efficacy of VX-809 by Rac1 activation, but the actin-binding domain of ezrin was not required for the increase in efficacy. Thus, rather than mainly directing anchoring of F508del-CFTR to the actin cytoskeleton, induction of ezrin activation by Rac1 signaling triggered a conformational change in NHERF1, which was then able to bind and stabilize misfolded CFTR at the plasma membrane. These insights into the cell surface stabilization of CFTR provide new targets to improve treatment of CF.